Independent effects of kidney function and cholesterol efflux on cardiovascular mortality - Ritsch, Andreas; Hunjadi, Monika; Stojakovic, Tatjana; Scherberich, Jürgen E.; Silbernagel, Günther; Scharnagl, Hubert; Delgado Gonzales de Kleber, Graciela; Kleber, Marcus E.; März, Winfried (Biomedicines, 2022)
Background: Impaired renal function is associated with cardiovascular and all-cause mortality. In the general population, HDL-cholesterol is associated with cardiovascular events, which is not true in patients with chronic kidney disease (CKD). This has been attributed to abnormal HDL function in CKD. Methods: In this study, we analyzed the association of genetic markers for kidney function with cholesterol efflux capacity as one of the major HDL functions, as well as with cardiovascular mortality, in 2469 patients of the Ludwigshafen Risk and Cardiovascular Health Study who all underwent coronary angiography. Results: A genetic score of 53 SNPs associated with GRF and the uromodulin SNP rs12917707 were inversely correlated with cholesterol efflux capacity. This was in line with the observed association between cholesterol efflux capacity and kidney function in these patients. Adjustment for eGFR and uromodulin as markers of kidney function did not affect the relationship between cholesterol efflux and cardiovascular mortality. Conclusions: Our data propose the view that cholesterol efflux and kidney function are exerting their effects on cardiovascular mortality via different and independent pathways. Decreased cholesterol efflux may therefore not mediate the effects of impaired kidney function on cardiovascular mortality.